Interwar Period in Polish History Handbooks of the Fifty Years (1945 – 1994) - Wagner, Barbara (Journal of Vasyl Stefanyk Precarpathian National University, 2023)
The article presents the theoretical aspects of teaching Polish history at schools from 1945 to 1994. The author emphasizes that the Poles undeniably are a nation whose identity and national character have been shaped to a great extent by tradition and history education. It has been proven that the national character is formed in the course of history and the factors contributing to it may be easily recognized. When the national character manages to specify itself it tends to stability and rejection or assimilation destructive influence. It turned out that of great importance is that the national character is never exclusively unique or uncommon; it is rather a combination of widespread features typical for many nations. These two trends of historical influence existed side by side despite their contrary character which was especially clear within fifty years. The formation of the historical consciousness of the contemporary Poles has been proudly influenced by the image of the interwar period of 1918-1939. The author concludes that the expansion of history propaganda function did not result in a change in social awareness of history. People rejected the official history (even reliably presented facts) since they still had in mind the practice of the Stalin period and the faults of the recent history; instead, they resorted to 'private' history which was frequently based on books of the 19th-century authors.